Awareness and Practices of Solid Waste Management among Grade 12 HUMSS Students of Ipil Shepherd Montessori Center, Zamboanga Sibugay - Usman, Rushiel Ces; Pizzaras, Danielle Patrice Angeles; Malali, Einna Sabandal; Panistante, Yrle Cudal; Baruela, Ana Marie Sorino; Camposo, Melisa; Damasing, Sherlyn Fabilliar; Canete, Jean Dela Cerna; Abao, Drhea Mae Dandiopan; Benitez, Karen (Paedagogia: Jurnal Pendidikan, 2025)
This research investigates the level of awareness and practices towards solid waste management among Grade 12-HUMSS students of Ipil Montessori Academy, Philippines. Employing a descriptive-correlational quantitative design, the study involved 100 respondents (64 females and 36 males) aged 16–29 years. Data were gathered through a structured questionnaire and analyzed using descriptive statistics, independent samples t-test, and Pearson correlation to determine differences and relationships between variables. The findings revealed that students generally demonstrated a moderate level of awareness of solid waste management, particularly in their knowledge of definitions, risks, prohibited activities, and their own roles and responsibilities. Television and radio emerged as the most common sources of awareness, while reduction and reuse were the most frequently practiced methods of managing waste. Gender was not found to significantly influence either awareness or practices. Importantly, this research found that students acknowledged the importance of waste management for environmental health and sustainability, yet gaps remained in their understanding of relevant laws and school interventions. The study concludes that although students exhibit positive attitudes and practices towards responsible waste management, strengthening environmental education is essential to address existing knowledge gaps and encourage more sustainable behaviors. These findings imply the need for schools and policymakers to reinforce awareness programs, integrate legal and practical aspects of waste management into the curriculum, and cultivate long-term environmental responsibility among students.